تدابير الوقاية من الأمراض النّفسيّة المعاصرة دراسة تحليليّة من منظور الشّريعة الإسلاميّة - Muneer Ali Abdul Rab; Mahmoud Mohamed Ali Mahmoud Edris; Baidar Mohammed Mohammed Hasan; Setiyawan bin Gunardi; Abdul Manan Ismail; Syaryanti Hussin (USIM Press, 2024)
The 4th International Conference of Postgraduate Students and Academics in Syariah and Law 2023 (4th INPAC 2023) “Pengajian Syariah dan Undang-Undang dalam Mendepani Cabaran Kontemporari” Editors (Malay & English) : Nur Aina Abdulah, Mashitah Abdul Mutalib, Siti Syahirah Saffinee, Nur Al-Farhain Kamaruzaman, Zizi Azlinda Mohd Yusof, Mualimin Mochammad Sahid, Hussein 'Azeemi Abdullah Thaidi, Muhammad Aunurrochim Mas'ad Saleh, Haliza A. Shukor, Mariam Saidona Tagoranao. Editors (Arabic) : Munir Ali Abdul Rab, Mahmoud Mohamed Ali Mahmoud Edris, Nurul Ain Binti Hazram, Ahmad Zaki Salleh, Baidar Mohammed Mohammed Hasan, Setiyawan Bin Gunardi, Fithriah Wardi, Lutfi Bin Mohamed Zain Organizer: Faculty of Syariah and Law 17 March 2023